Integrating the audience into a theatre performance using mobile devices. Issue 1 (1st April 2014) - B. Owen, Charles; Dobbins, Alison; Rebenitsch, Lisa
Abstract : Purpose: – Theatre Engine is a three-phase project exploring the integration of mobile devices such as smart phones and tablet computers as user interaction mechanisms for live theatrical performances. This paper aims to describe the technical details for the first performance in the series: transitions, including system design, user interface details, and lessons learned. Design/methodology/approach: – The Theatre Engine project consists of a network of mobile Android-based devices that communicate with a server managing a live theatrical performance. Additional systems provide projected graphics within the performance space, dynamic instructions to live musicians, and control of theatrical equipment including robotic lighting. The system is under the live control of a stage managers and show runner. The first phase produced the performance transitions, where live and virtual dancers interacted with audience members. Findings: – The user activities are described in the context of manipulations and the effects of those manipulations and a classification of the roles of users as active participants in the performance is proposed. The concept of blurring the distinction between real and virtual is explored. Originality/value: – Technological advances make it possible for the audience to be an active participant in a performance, converting a passive theatrical experience to an active and immersive experience. Theatre Engine is a new approach to the integration of mobile devices into the theatre and a test-bed for new user interface ideas.